MENINGKATKAN MOTIVASI BELAJAR KELAS XI DI SMK DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Rowiyah Rowiyah; Aflich Yusnita Fitrianna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The following research relates to the use of problem based learning (PBL) models in mathematics learning aimed at increasing student learning motivation. The subjects in this study were students of class XI in one of state vocational schools in Cimahi. Questionnaires and observation sheets as instruments used in this study. Research is carried out a number of two cycles, each cycle for one study, each cycle there are four main activities, namely planning, implementation, observation and reflection. The data collection technique in this study used questionnaires and observation sheets. The data analysis technique is descriptive qualitative, so that research results are obtained that show that there is an increase in student learning motivation in each cycle.This can be seen from the increase in students' positive motivation obtained from the questionnaire given. Because learning with a problem based learning (PBL) model has characteristics that are able to make students easily understand the material conveyed and motivate students to learn mathematics for the better.